Oxidation Parameters of Sardine Oil Extracted from Fish Oil Emulsion - Haryati, Kristina (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Fish oil contains polyunsaturated fatty acids, so it is made into an emulsion preparation. The emulsifier used must be able to protect the oil during storage. The purpose of this study was to determine the oxidation parameters of sardine fish oil extracted from the emulsion. The research method was divided into 2 stages, namely oil extraction from the emulsion using the Bligh and Bryer methods; oxidation parameter testing carried out included determining the levels of free fatty acids (FFA), peroxide value (PV), acid value (AV), anisidine value (AnV), and total oxidation (Totoks) based on AOCS 1998. The results showed that the highest FFA value was in formula 3:2 followed by formula 1:2, 1:1, and the lowest was in formula 3:1. The highest PV value was in formula 1:2 followed by formula 1:1, 3:2, and the lowest was in formula 3:1. The highest AV value was in formula 3:2 followed by formula 1:2, 1:1, and the lowest was in formula 3:1. The highest AnV and Totoks values were found in formula 1:2 followed by formula 1:1, 3:2, and the lowest was in formula 3:1. These findings indicate that the oil extracted from formula 3:1 has lower oxidation parameter values than the others. Thus, this study indicates that the oxidation parameters of the oil extracted from the emulsion have not met the IFOS standard, and another emulsifier is needed to protect the oil in the form of an emulsion preparation during storage.